The beholden - Clarke, Cassandra Rose, 1983- (Erewhon Books, 2022)
In the latest novel by critically acclaimed author Cassandra Rose Clarke, two noblewomen and the pirate who once accompanied them to seek a bargain with a goddess find themselves at the center of a conflict between the immortal being Decay and the Emperor himself, as the goddess calls on them to repay their debt by seeking out this elusive god, before the world crumbles around them all.